(untitled) (Bioscience Journal, 2018)
A quantitative study was conducted in the municipality of Aracaju/State of Sergipe - SE, Brazil, to construct and analyse the ecomap of users (216 users) who received a home visit from the Family Health Teams (Equipes de Saúde da Família). The study showed that half of the users (50.5%) were over 60 years old, 77.8% were female, 68.0% had a low educational level, 49.1% were retired, 83.3% reported being bedridden, 53.2% reported a chronic injury as the reason for having the visit, 62.5% did not know the nursing assistant professional, 58.8% had a family caregiver, 94.4% considered the visit important, and 75.9% were informed about their right to a visit but considered it a privilege. The home visit is perfectly feasible, humanising and welcoming; it is a unique opportunity to immerse into and get to know the environment of families, delivering services in a more humane and welcoming space.